Preparation method and application of high-performance oriented crystal nanowire composite solid electrolyte

Directed LLTO nanowires are prepared through coaxial electrospinning technology and recombined with polymer electrolytes, which solves the problem of uncontrollable crystal structure of inorganic fast ion conductors, significantly improves lithium ion transfer capability and electrochemical performance, and realizes all-solid-state lithium battery Excellent performance and stability.

CN119208713APending Publication Date: 2024-12-27ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411306320.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The crystal structure of existing inorganic fast ion conductors is uncontrollable, resulting in significant differences in lithium ion conductivity and low conductivity, making it difficult to build a long-range continuous fast transmission channel.

Method used

Coaxial electrospinning technology was used to prepare LLTO nanowires with a 'core-sheath' structure. The strong adsorption effect of the PVP sheath on the crystal plane of the LLTO crystal (110) is induced to grow in the c-axis direction and recombined with the polymer electrolyte. , construct directional crystal nanowire composite solid electrolyte.

Benefits of technology

It significantly improves lithium ion transfer capability and electrochemical performance, achieves better lithium ion transfer performance and stability than traditional solid electrolytes, and enhances the room temperature cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208713A_ABST
    Figure CN119208713A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state electrolytes for all-solid-state lithium batteries, and discloses a preparation method and application of a high-performance oriented crystal nanowire composite solid-state electrolyte, and the preparation method comprises the following steps: preparing a PVP / LLTO-CNW coaxial nanowire by adopting a PVP spinning solution and an LLTO precursor solution through a coaxial electrostatic spinning technology; the PVP / LLTO-CNW coaxial nanowire is sintered in the air atmosphere, and an LLTO nanowire frame with an oriented crystal structure is obtained; and preparing a polymer electrolyte: repeatedly dropwise adding a polymer electrolyte solution into the LLTO nanowire frame with the oriented crystal structure in an inert gas atmosphere, drying until the LLTO nanowire frame is completely embedded into a polymer matrix, and performing vacuum drying to obtain the high-performance oriented crystal nanowire composite solid electrolyte. The high-performance oriented crystal nanowire composite solid electrolyte prepared by the preparation method disclosed by the invention has more excellent lithium ion transmission performance and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes for all-solid-state lithium batteries, and in particular to a preparation method and application of a high-performance oriented crystal nanowire composite solid electrolyte. Background Art

[0002] Lithium batteries have advantages such as high voltage and high energy density, and they dominate the application of rechargeable batteries. The electrolyte used in traditional lithium batteries contains a large amount of flammable organic solvents. When the battery is hit, overcharged, or has an internal short circuit, there are safety hazards such as electrolyte leakage, combustion and explosion. Using solid electrolytes instead of traditional organic electrolytes can fundamentally solve the above risks. Compared with polymer solid electrolytes and inorganic solid electrolytes, composite solid electrolytes can synergistically exert the advantages of organic and inorganic phases. The inorganic phase with high conductivity is the basis for building a low-resistance transmission channel in the composite solid electrolyte.

[0003] Inorganic fast ion conductors have been widely studied due to their high bulk ionic conductivity and excellent physicochemical stability at room temperature. However, the uncontrollable crystal structure (including crystal phase, grain boundary, etc.) in fast ion conductors leads to significant differences in the ionic conductivity of the inorganic electrolytes reported so far, and all of them are 1 to 2 orders of magnitude lower than the bulk ionic conductivity. According to the principle of entropy increase, crystals that grow freely in open space are always arranged in a specific structure to ensure thermodynamic stability. Differences in the potential energy surface in the crystal will lead to the Li + The transfer energy barrier is different, resulting in Li + The transfer is highly anisotropic. For LLTO crystals, due to the presence of a large number of vacancies in the La-poor layer, the c-axis becomes the fastest Li + Transfer path. Local microenvironments such as defects and distortions are constructed by methods such as element doping, but only rapid Li + On the other hand, the grain boundaries between grains of different orientations in the electrolyte also cause the overall conductivity of the electrolyte to be several orders of magnitude lower than the bulk conductivity. Therefore, how to construct a long-range continuous fast transfer crystal phase by directly controlling the growth process of fast ion conductor crystals is the key to breaking the transfer limit.

[0004] Confinement and induction are effective strategies for controlling the anisotropic growth of inorganic crystals. For physical confinement processes, inorganic materials are usually used to construct platforms with nanoscale confined spaces. In the constructed confined space, changes in the physicochemical microenvironment can promote the controlled growth of crystals, but there is an inherent disadvantage that ion transfer is blocked due to the difficulty in removing the non-ion-transmitting inorganic phase. In contrast, the interactions formed by inducers such as surfactants, capping agents, polymers or ions can be adsorbed on specific crystal faces (such as metal-organic frameworks, electrode materials), which provides another way to induce anisotropic growth of crystals and control the evolution of ordered structures. And the inducer can be completely removed in subsequent operations. Therefore, chemical induction may be a practical and effective strategy to achieve directional and controllable crystal growth of fast ion conductors, but how to achieve all-round induction of the crystal structure of fast ion conductors and apply it to the construction of composite solid electrolytes remains a challenge.

[0005] Therefore, there is an urgent need for the preparation method and application of high-performance oriented crystal nanowire composite solid electrolytes to solve the above technical problems. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation method and application of a high-performance oriented crystal nanowire composite solid electrolyte in view of the development status and existing problems of solid electrolytes for all-solid-state lithium batteries. The high-performance oriented crystal nanowire composite solid electrolyte exhibits a more excellent lithium ion transfer ability than traditional composite solid electrolytes.

[0007] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0008] A method for preparing a high-performance oriented crystal nanowire composite solid electrolyte comprises the following steps:

[0009] S1, Preparation of coaxial nanowires with a "core-sheath" structure:

[0010] S1.1, dissolving PVP in DMF to obtain PVP spinning solution;

[0011] S1.2, dissolving Ti(OC4H9)4, LiNO3, La(NO3)3·6H2O and acetic acid in DMF to obtain LLTO precursor solution;

[0012] S1.3, using the PVP spinning solution obtained in step S1.1 as the sheath solution, and the LLTO precursor solution obtained in step S1.2 as the core solution, spinning the above solutions on a rotating drum receiver using coaxial electrospinning technology under high voltage electric field conditions at different propulsion speeds; after drying, PVP / LLTO-CNW coaxial nanowires with a "core-sheath" structure are obtained;

[0013] S2, sintering the PVP / LLTO-CNW coaxial nanowires in an air atmosphere to obtain an LLTO nanowire framework with an oriented crystal structure;

[0014] S3, preparation of polymer electrolyte solution:

[0015] dissolving polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide in an acetonitrile solvent under an inert gas atmosphere such as nitrogen or argon to obtain a polymer electrolyte solution;

[0016] S4, repeatedly dropping the polymer electrolyte solution into the LLTO nanowire framework with a directional crystal structure under an inert gas atmosphere such as nitrogen or argon and drying until the LLTO nanowire framework is completely embedded in the polymer matrix; finally, vacuum drying is performed to obtain a high-performance directional crystal nanowire composite solid electrolyte.

[0017] Preferably, in step S1.1, the average molecular weight of PVP is 1.3 million; and the mass fraction of PVP in the PVP spinning solution is 10-22%.

[0018] Preferably, in step S1.2, the molar ratio of Ti(OC4H9)4, LiNO3, and La(NO3)3·6H2O is 1:0.38:0.557; the mass ratio of Ti(OC4H9)4, LiNO3, and La(NO3)3·6H2O to DMF is 1.2-2.2:1, and the unit for comparison is g:mL; the volume ratio of DMF to acetic acid is 1:0.05-0.3.

[0019] Preferably, in step S1.3, the propulsion speed of the sheath solution is 0.2 to 0.8 mL / h, and the propulsion speed of the core solution is 0.05 to 0.4 mL / h.

[0020] Preferably, in step S1.3, the voltage of the high voltage electric field is 10-20 kV, and the rotation speed of the drum receiver is 100-900 r / min.

[0021] Preferably, in step S2, the sintering temperature is 800-1100°C, the sintering and heat preservation time is 1-4 hours, and the heating and cooling rate of the sintering process is 1-10°C / min.

[0022] Preferably, in step S3, the molecular weight of polyethylene oxide is 300,000 to 2,000,000, the mass ratio of polyethylene oxide to lithium bis(trifluoromethanesulfonyl)imide is 2 to 5:1; and the concentration of polyethylene oxide in the polymer electrolyte solution is 1 to 6 mg / mL.

[0023] Preferably, in step S4, the drying temperature of the drying step is 30-55° C., and the drying time for each drying step is 0.5-3 h; the drying temperature of the vacuum drying process is 50-70° C., and the drying time is 24-72 h.

[0024] Preferably, the mass fraction of the LLTO nanowire framework in the high-performance oriented crystalline nanowire composite solid electrolyte obtained in step S4 is 30-75%, and the thickness of the high-performance oriented crystalline nanowire composite solid electrolyte is 20-120 μm.

[0025] Preferably, the inert gas is one of nitrogen, argon, helium, neon, krypton and xenon.

[0026] Specifically, step S1 includes the following steps:

[0027] S1 Preparation of coaxial nanowires with a "core-sheath" structure:

[0028] S1.1. Dissolve PVP (polyvinyl pyrrolidone) in DMF (N, N-dimethylformamide), and stir until completely dissolved to obtain PVP spinning solution; the average molecular weight of PVP is 1.3 million (K88-96); in the PVP spinning solution, the mass fraction of PVP is 10-22%.

[0029] S1.2, dissolve Ti(OC4H9)4, LiNO3 (15% excess), La(NO3)3·6H2O and acetic acid in DMF in a molar ratio of 1:0.38:0.557, and stir until completely dissolved to obtain an LLTO precursor solution; in the LLTO precursor solution, the mass volume ratio between the precursor (Ti(OC4H9)4, LiNO3 (15% excess), La(NO3)3·6H2O) and the DMF solvent is (1.2~2.2) g:1 mL, and the volume ratio of DMF to acetic acid is 1:0.05~0.3.

[0030] S1.3, using the PVP spinning solution obtained in step S1.1 as the sheath solution and the LLTO precursor solution obtained in step S1.2 as the core solution, and using coaxial electrospinning technology to spin the above solutions on a rotating drum receiver under high voltage electric field conditions with the aid of different propulsion speeds, and obtaining PVP / LLTO-CNW coaxial nanowires after drying; the propulsion speed of the sheath solution is 0.2-0.8 mL / h, and the propulsion speed of the core solution is 0.05-0.4 mL / h; the voltage of the high voltage electric field is 10-20 kV, and the rotation speed of the drum receiver is 100-900 r / min.

[0031] Specifically, step S2 includes the following steps:

[0032] S2, slowly heating the PVP / LLTO-CNW coaxial nanowires to 800-1100°C in an air atmosphere for sintering, and keeping the temperature for 1-4 hours to obtain an LLTO nanowire framework with a directional crystal structure (abbreviated as LLTO-CNW); the heating and cooling rate of the sintering process is 1-10°C / min.

[0033] Specifically, step S3 includes the following steps:

[0034] S3, preparation of polymer electrolyte solution:

[0035] In an inert gas atmosphere such as nitrogen or argon, polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide are dissolved in an acetonitrile solvent in a certain ratio, and stirred until completely dissolved to obtain a polymer electrolyte solution; the molecular weight of polyethylene oxide is 300,000 to 2,000,000, and the mass ratio of polyethylene oxide to lithium bis(trifluoromethanesulfonyl)imide is 2 to 5:1; the concentration of polyethylene oxide in the polymer electrolyte solution is 1 to 6 mg / mL.

[0036] Specifically, step S4 includes the following steps:

[0037] S4, under an inert gas atmosphere such as nitrogen or argon, the obtained polymer electrolyte solution is repeatedly added dropwise to the LLTO nanowire framework with a directional crystal structure obtained in step S2 and dried (rather than crushed and mixed with the polymer electrolyte solution to prepare a casting solution), until the LLTO nanowire framework is completely embedded in the polymer matrix (dried polymer electrolyte solution), and finally vacuum dried to obtain a high-performance directional crystal nanowire composite solid electrolyte. In step S4, the drying temperature of the drying step is 30-55°C, and the drying time is 0.5-3h each time; the drying temperature of the vacuum drying process is 50-70°C, and the drying time is 24-72h; the thickness of the obtained high-performance directional crystal nanowire composite solid electrolyte is 20-120μm, and the mass fraction of the LLTO nanowire framework in the high-performance directional crystal nanowire composite solid electrolyte is 30-75%.

[0038] The present invention also includes the use of the high-performance oriented crystal nanowire composite solid electrolyte prepared by the above preparation method in an all-solid-state lithium battery.

[0039] The present invention firstly adopts PVP solution as sheath solution and Li 0.33 La 0.557TiO3 (LLTO) precursor solution was used as the core solution, and coaxial nanowires were prepared by coaxial electrospinning technology, which effectively avoided the full mixing between PVP and LLTO precursors in traditional uniaxial nanowires, thereby preventing the high oxygen-rich PVP molecules from encapsulating the LLTO precursor and preventing the negative impact on the nucleation and growth process of LLTO crystals. Subsequently, high-temperature sintering was carried out, and the strong adsorption of the PVP sheath on the (110) crystal surface of the LLTO crystal induced the LLTO crystal to grow preferentially along the c-axis direction with the strongest transmission ability, thereby obtaining an LLTO nanowire framework with a directional crystal structure; finally, the acetonitrile solution of polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide was repeatedly dripped on the LLTO nanowire framework and dried (rather than crushed and mixed with a polymer electrolyte solution to prepare a casting solution), until the LLTO nanowire framework was completely embedded in the polymer matrix, and a high-performance directional crystal nanowire composite solid electrolyte was obtained. The high-performance oriented crystal nanowire composite solid electrolyte prepared by the present invention can construct a low-resistance and long-range continuous lithium ion transfer channel in the electrolyte, thereby enhancing the lithium ion transfer behavior and improving the electrochemical performance, and exhibiting better battery performance than traditional solid electrolytes.

[0040] The high-performance oriented crystal nanowire composite solid electrolyte prepared by the present invention exhibits excellent lithium ion transfer ability. Coaxial nanowires with PVP sheath and LLTO precursor core are prepared by coaxial electrospinning technology. Different from traditional uniaxial nanowires, coaxial nanowires effectively avoid sufficient mixing between PVP and LLTO precursor, thereby preventing the high oxygen-rich PVP molecules from encapsulating the LLTO precursor and preventing the negative impact on the nucleation and growth of LLTO crystals. During the high-temperature sintering process, the strong adsorption of the PVP sheath on the LLTO crystal (110) crystal plane induces the LLTO crystal to grow preferentially along the c-axis direction with the strongest transfer ability, thereby obtaining a oriented crystal structure LLTO nanowire framework with high conductivity, and its ion conduction ability is two orders of magnitude higher than that of the LLTO nanowire obtained by the uniaxial nanowire; the oriented crystal nanowire composite solid electrolyte obtained after compounding with polyethylene oxide / bistrifluoromethanesulfonyl imide lithium constructs a long-range continuous low-resistance lithium ion transfer channel. In particular, by directly using the oriented crystal nanowire framework to repeatedly infiltrate the polymer electrolyte instead of crushing the nanowire framework and using the casting method to make a film, the nanowire framework can preserve the original interconnected state, which is conducive to the construction of a long-range continuous transmission channel. The oriented crystal nanowire composite solid electrolyte shows significantly improved lithium ion transfer capacity and stability. Applying this electrolyte to all-solid-state lithium batteries can achieve excellent electrochemical performance and safety performance.

[0041] The principle of the present invention is as follows:

[0042] 1) The coaxial nanowires prepared by the coaxial electrospinning technology of the present invention have the strongest adsorption capacity of the pre-constructed PVP sheath on the (110) crystal plane in LLTO, which promotes the crystal to grow preferentially along the c-axis direction where lithium ion transfer is fastest during nucleation and growth, significantly enhancing the bulk transfer capacity of LLTO; at the same time, the highly oriented crystal structure reduces the grain boundaries and significantly improves the grain boundary conductivity of the nanowires. Unlike traditional uniaxial nanowires, coaxial nanowires effectively avoid full mixing between PVP and LLTO precursors, thereby preventing the high oxygen-rich PVP molecules from encapsulating the LLTO precursors and preventing negative effects on the nucleation and growth of LLTO crystals.

[0043] 2) The oriented crystal nanowire composite solid electrolyte prepared by compounding the oriented crystal nanowire framework with the polymer electrolyte exhibits excellent lithium ion conductivity and physical and chemical stability. In particular, the oriented crystal nanowire framework is directly used to repeatedly infiltrate the polymer electrolyte, rather than crushing the nanowire framework and using the casting method to make a film. The nanowire framework can preserve the original interconnected state, which is conducive to the construction of a long-range continuous transmission channel.

[0044] 3) Compared with traditional polymer solid electrolytes and traditional uniaxially spun nanowire composite electrolytes, all-solid-state lithium batteries assembled with oriented crystal nanowire composite solid electrolytes exhibit excellent room temperature cycling stability.

[0045] In summary, the present invention prepares nanowires with oriented crystal structures through coaxial electrospinning technology, provides a low-resistance transmission path for composite solid electrolytes, and strengthens the stability of solid electrolytes. From the perspective of preparation ideas, it is mainly through the construction of coaxial nanowires to strengthen the induction effect of the PVP sheath on the growth of LLTO crystals, thereby obtaining LLTO nanowires with more rapid transmission paths while reducing grain boundaries, and then compounding with polymer electrolytes to obtain high-performance composite solid electrolyte membranes.

[0046] Beneficial effects of the present invention:

[0047] 1. The coaxial electrospinning technology used in the technical solution of the present invention is easy to implement, easy to scale up for production, and has high production efficiency.

[0048] 2. The oriented crystalline nanowires with abundant c-axis transmission paths prepared by the present invention have ultra-high bulk conductivity (>3×10 -3 S / cm), and the highly oriented crystal structure reduces the grain boundaries, making its grain boundary conductivity exceed 1×10 -3 S / cm.

[0049] 3. The high-performance oriented crystal nanowire composite solid electrolyte prepared by the present invention has more excellent lithium ion transfer performance and stability; the assembled all-solid-state lithium battery can stably cycle 300 times at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 A schematic diagram of the present invention for preparing high-performance oriented crystalline nanowires by coaxial electrospinning technology;

[0051] Figure 2 This is a physical picture of the PVP / LLTO-CNW coaxial nanowires obtained in step 1) of Example 1 of the present invention;

[0052] Figure 3 This is a scanning electron microscope image of the PVP / LLTO-CNW coaxial nanowires obtained in step 1) of Example 1 of the present invention;

[0053] Figure 4 This is a scanning electron microscope image of the PVP sheath of the PVP / LLTO-CNW coaxial nanowire obtained in step 1) of Example 1 of the present invention after being treated with acetone;

[0054] Figure 5 This is a scanning electron microscope image of the PVP / LLTO-NW uniaxial nanowires obtained in step 1) of Comparative Example 1 of the present invention;

[0055] Figure 6 This is a scanning electron microscope image of the LLTO-CNW nanowire framework obtained in step 2) of Example 1 of the present invention;

[0056] Figure 7 This is a scanning electron microscope image of the LLTO-NW obtained in step 2) of comparative example 1 of the present invention;

[0057] Figure 8 XRD spectra of the LLTO-CNW nanowire framework of Example 1 of the present invention, the LLTO-NW of Comparative Example 1, and the LLTO nanoparticles;

[0058] Fig. 9 This is a scanning electron microscope image of the high-performance oriented crystal nanowire composite solid electrolyte PL / LLTO-CNW obtained in step 4) of Example 1 of the present invention;

[0059] Fig.10 ion conductivity diagrams of the PL / LLTO-CNW electrolyte of Example 1 of the present invention, the PL / LLTO-NW electrolyte of Comparative Example 1, and the PL electrolyte of Comparative Example 2;

[0060] Fig.11This is a room temperature cycling performance diagram of an all-solid-state lithium battery assembled with the PL / LLTO-CNW electrolyte of Example 1 of the present invention, the PL / LLTO-NW electrolyte of Comparative Example 1, and the PL electrolyte of Comparative Example 2. DETAILED DESCRIPTION

[0061] The present invention is further described below with reference to specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0062] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0063] There is no particular limitation on the purity of all raw materials in the present invention, and the present invention preferably adopts the conventional purity used in the art.

[0064] The devices used in the present invention are not particularly limited and can be any of the commonly used devices in the art.

[0065] Embodiment 1:

[0066] The preparation method of high-performance oriented crystal nanowire composite solid electrolyte, the detailed steps are as follows:

[0067] 1) Preparation of coaxial nanowires with a "core-sheath" structure:

[0068] a. Weigh 1.5 g of PVP with an average molecular weight of 1.3 million (K88-96) and dissolve it in 7 mL of DMF. Stir until completely dissolved to obtain a PVP spinning solution with a mass fraction of 17.6%;

[0069] b. Weigh 0.147g LiNO3 and 1.417g La(NO3)3·6H2O respectively and dissolve them in 2mL DMF. After dissolution, add 0.2mL acetic acid, then slowly add 2g Ti(OC4H9)4, and stir until completely dissolved to obtain LLTO precursor solution.

[0070] c. The PVP spinning solution obtained in step a is used as the sheath solution, and the LLTO precursor solution obtained in step b is used as the core solution, wherein the propulsion speed of the PVP sheath solution is 0.5 mL / h, and the propulsion speed of the LLTO core solution is 0.2 mL / h. The above solution is spun on a drum receiver at 300 r / min using coaxial electrospinning technology under a high voltage electric field of 15 kV, and dried at 60°C for 24 hours to obtain PVP / LLTO-CNW coaxial nanowires;

[0071] 2) slowly heating the PVP / LLTO-CNW coaxial nanowires obtained in step c to 900° C. at 10° C. / min in an air atmosphere and maintaining the temperature for 2 h to obtain an LLTO nanowire framework having an oriented crystal structure, which is referred to as an LLTO-CNW nanowire framework;

[0072] 3) Preparation of polymer electrolyte solution: Under an inert gas atmosphere such as nitrogen or argon, 1 g of polyethylene oxide with an average molecular weight of 600,000 and 0.3625 g of lithium bis(trifluoromethanesulfonyl)imide were weighed and dissolved in 400 mL of acetonitrile solvent, and stirred until completely dissolved to obtain a polymer electrolyte solution with a polyethylene oxide concentration of 2.5 mg / mL;

[0073] 4) In an inert gas atmosphere such as nitrogen or argon, the obtained polymer electrolyte solution is repeatedly added dropwise to the LLTO nanowire framework with a directional crystal structure obtained in step 2) and dried at 45°C for 2 hours until the nanowire framework is completely embedded in the polymer matrix. Finally, after vacuum drying at 60°C for 48 hours, a high-performance directional crystal nanowire composite solid electrolyte is obtained, which is recorded as PL / LLTO-CNW.

[0074] The mass fraction of the LLTO nanowire framework in the PL / LLTO-CNW electrolyte of this embodiment is 58%, and the thickness of the PL / LLTO-CNW electrolyte is 50 μm.

[0075] The high-performance composite solid electrolyte membrane prepared in Example 1 is assembled into an all-solid-state lithium battery.

[0076] In this embodiment, the positive electrode material of the all-solid-state lithium battery is lithium iron phosphate, specifically: lithium iron phosphate, binder PVDF and conductive carbon black are mixed in a mass ratio of 8:1:1 and dispersed in N-methylpyrrolidone solvent to obtain a slurry, and the positive electrode slurry is evenly coated on aluminum foil using a cast coater, and vacuum dried at 110°C for 48 hours, and finally compacted using a roller press and cut to a positive electrode disc with a diameter of 12mm using a slicer and assembled into an all-solid-state lithium battery. The negative electrode material of the all-solid-state lithium battery is a commercially available lithium foil with a diameter of 16mm. The obtained battery is recorded as LFP|PL / LLTO-CNW|Li battery.

[0077] The performance of the assembled battery was tested. After 300 cycles at 25°C and 0.5C, the discharge capacity was 120.8 mAh g -1 .

[0078] Embodiment 2:

[0079] The preparation method of high-performance oriented crystal nanowire composite solid electrolyte, the detailed steps are as follows:

[0080] 1) Preparation of coaxial nanowires with a "core-sheath" structure:

[0081] a. Weigh 1.5 g of PVP with an average molecular weight of 1.3 million (K88-96) and dissolve it in 6 mL of DMF. Stir until completely dissolved to obtain a PVP spinning solution with a mass fraction of 20%;

[0082] b. Weigh 0.147 g LiNO3 and 1.417 g La(NO3)3·6H2O respectively and dissolve them in 2.5 mL DMF. After dissolution, add 0.15 mL acetic acid, then slowly add 2 g Ti(OC4H9)4, and stir until completely dissolved to obtain LLTO precursor solution.

[0083] c. The PVP spinning solution obtained in step a is used as the sheath solution, and the LLTO precursor solution obtained in step b is used as the core solution, wherein the propulsion speed of the PVP sheath solution is 0.6 mL / h, and the propulsion speed of the LLTO core solution is 0.15 mL / h. The above solution is spun on a drum receiver at 400 r / min using coaxial electrospinning technology under a high voltage electric field of 17 kV, and dried at 60°C for 24 hours to obtain PVP / LLTO-CNW-2 coaxial nanowires;

[0084] 2) The PVP / LLTO-CNW coaxial nanowires obtained in step c were slowly heated to 800° C. at 8° C. / min in an air atmosphere and kept for 4 h for calcination to obtain a LLTO nanowire framework with a smaller diameter and a directional crystal structure, which was recorded as LLTO-CNW-2;

[0085] 3) Preparation of polymer electrolyte solution: Under an inert gas atmosphere such as nitrogen or argon, 1 g of polyethylene oxide with an average molecular weight of 1 million and 0.5 g of lithium bis(trifluoromethanesulfonyl)imide were weighed and dissolved in 600 mL of acetonitrile solvent, and stirred until completely dissolved to obtain a polymer electrolyte solution with a polyethylene oxide concentration of 1.7 mg / mL;

[0086] 4) In an inert gas atmosphere such as nitrogen or argon, the obtained polymer electrolyte solution is repeatedly added dropwise to the LLTO nanowire framework with a directional crystal structure obtained in step 2) and dried at 35°C for 3 hours until the nanowire framework is completely embedded in the polymer matrix. Finally, after vacuum drying at 55°C for 72 hours, a high-performance directional crystal nanowire composite solid electrolyte is obtained, which is recorded as PL / LLTO-CNW-2.

[0087] The mass fraction of the LLTO nanowire framework in the PL / LLTO-CNW-2 electrolyte of this embodiment is 40%, and the thickness of the PL / LLTO-CNW-2 electrolyte is 40 μm.

[0088] Embodiment 3:

[0089] The preparation method of high-performance oriented crystal nanowire composite solid electrolyte, the detailed steps are as follows:

[0090] 1) Preparation of coaxial nanowires with a "core-sheath" structure:

[0091] a. Weigh 1.5 g of PVP with an average molecular weight of 1.3 million (K88-96) and dissolve it in 10.5 mL of DMF. Stir until completely dissolved to obtain a PVP spinning solution with a mass fraction of 12.5%;

[0092] b. Weigh 0.147 g LiNO3 and 1.417 g La(NO3)3·6H2O respectively and dissolve them in 1.7 mL DMF. After dissolution, add 0.25 mL acetic acid, then slowly add 2 g Ti(OC4H9)4, and stir until completely dissolved to obtain LLTO precursor solution.

[0093] c. The PVP spinning solution obtained in step a is used as the sheath solution, and the LLTO precursor solution obtained in step b is used as the core solution, wherein the propulsion speed of the PVP sheath solution is 0.45 mL / h, and the propulsion speed of the LLTO core solution is 0.23 mL / h. The above solution is spun on a drum receiver at 200 r / min using coaxial electrospinning technology under a high voltage electric field of 12 kV, and dried at 60°C for 24 hours to obtain PVP / LLTO-CNW-3 coaxial nanowires;

[0094] 2) The PVP / LLTO-CNW coaxial nanowires obtained in step c were slowly heated to 1000° C. at 5° C. / min in an air atmosphere and maintained for 1 h for calcination to obtain an LLTO nanowire framework with an oriented crystal structure, which was recorded as LLTO-CNW-3;

[0095] 3) Preparation of polymer electrolyte solution: Under an inert gas atmosphere such as nitrogen or argon, 1 g of polyethylene oxide with an average molecular weight of 300,000 and 0.2 g of lithium bis(trifluoromethanesulfonyl)imide were weighed and dissolved in 200 mL of acetonitrile solvent, and stirred until completely dissolved to obtain a polymer electrolyte solution with a polyethylene oxide concentration of 5 mg / mL;

[0096] 4) In an inert gas atmosphere such as nitrogen or argon, the obtained polymer electrolyte solution is repeatedly added dropwise to the LLTO nanowire framework with a directional crystal structure obtained in step 2) and dried at 50°C for 1 h until the nanowire framework is completely embedded in the polymer matrix. Finally, after vacuum drying at 65°C for 30 h, a high-performance directional crystal nanowire composite solid electrolyte is obtained, which is recorded as PL / LLTO-CNW-3.

[0097] The mass fraction of the LLTO nanowire framework in the PL / LLTO-CNW-3 electrolyte of this embodiment is 70%, and the thickness of the PL / LLTO-CNW-3 electrolyte is 80 μm.

[0098] Comparative Example 1:

[0099] 1) Preparation of uniaxial nanowires:

[0100] a. Weigh 0.5 g of PVP with an average molecular weight of 1.3 million (K88-96) and dissolve it in 3.86 mL of DMF. Stir until completely dissolved to obtain a PVP solution with a mass fraction of 12%;

[0101] b. Weigh 0.264 g LiNO3 and 2.55 g La(NO3)3·6H2O respectively and dissolve them in the PVP solution in step a. After dissolution, add 0.54 mL acetic acid, then slowly add 3.6 g Ti(OC4H9)4, and stir until completely dissolved to obtain a mixed spinning solution of LLTO precursor and PVP;

[0102] c. The mixed spinning solution obtained in step b was set to advance at a speed of 1.0 mL / h, and the solution was spun on a drum receiver at 300 r / min using a uniaxial electrospinning technique under a high voltage electric field of 15 kV, and dried at 60 ° C for 24 h to obtain PVP / LLTO-NW uniaxial nanowires;

[0103] 2) slowly heating the PVP / LLTO-NW uniaxial nanowire obtained in step c to 900° C. at 10° C. / min in an air atmosphere and maintaining the temperature for 2 h to obtain an LLTO nanowire framework, which is referred to as LLTO-NW;

[0104] 3) Preparation of polymer electrolyte solution: Under an inert gas atmosphere such as nitrogen or argon, 1 g of polyethylene oxide with an average molecular weight of 600,000 and 0.3625 g of lithium bis(trifluoromethanesulfonyl)imide were weighed and dissolved in 400 mL of acetonitrile solvent, and stirred until completely dissolved to obtain a polymer electrolyte solution with a polyethylene oxide concentration of 2.5 mg / mL;

[0105] 4) In an inert gas atmosphere such as nitrogen or argon, the obtained polymer electrolyte solution is repeatedly added dropwise to the LLTO-NW obtained in step 2) and dried at 45°C for 2 h until the nanowire framework is completely embedded in the polymer matrix. Finally, the nanowire composite solid electrolyte is obtained after vacuum drying at 60°C for 48 h, which is recorded as PL / LLTO-NW.

[0106] According to the method of Example 1, the corresponding battery was assembled using the nanowire composite solid electrolyte prepared in this comparative example, and was recorded as LFP|PL / LLTO-NW|Li battery.

[0107] Comparative Example 2:

[0108] 1) Preparation of polymer electrolyte solution: Under an inert gas atmosphere such as nitrogen or argon, 0.5 g of polyethylene oxide with an average molecular weight of 600,000 and 0.1812 g of lithium bis(trifluoromethanesulfonyl)imide were weighed and dissolved in 20 mL of acetonitrile solvent, and stirred until completely dissolved to obtain a polymer electrolyte solution;

[0109] 2) Pour the obtained polymer electrolyte solution into a polytetrafluoroethylene mold with an inner diameter of 100 mm × 100 mm under an inert gas atmosphere such as nitrogen or argon, dry at 35°C for 6 h to remove the volatilized acetonitrile, and then heat to 60°C and vacuum dry for 48 h to obtain a blank polymer electrolyte, which is recorded as PL.

[0110] According to the method of Example 1, the corresponding battery was assembled using the nanowire composite solid electrolyte prepared in this comparative example, and was recorded as LFP|PL|Li battery.

[0111] like Figure 1 As shown, it is a schematic diagram of preparing high-performance oriented crystalline nanowires by coaxial electrospinning technology in the present invention; Figure 1 It can be seen that the present invention prepares the nanowires through the coaxial electrospinning technology.

[0112] like Figure 2 As shown, it is a physical picture of the PVP / LLTO-CNW coaxial nanowires obtained in step 1) of Example 1 of the present invention; Figure 2 It can be seen that the PVP / LLTO-CNW membrane prepared by coaxial electrospinning technology is uniform and smooth.

[0113] like Figure 3 As shown, it is a scanning electron microscope image of the PVP / LLTO-CNW coaxial nanowires obtained in step 1) of Example 1 of the present invention; Figure 3 It can be seen that the PVP / LLTO-CNW prepared by coaxial electrospinning technology is uniform in size, with an average diameter of about 1000 nm.

[0114] like Figure 4 , which is a scanning electron microscope image of the PVP sheath of the PVP / LLTO-CNW coaxial nanowires obtained in step 1) of Example 1 of the present invention after being treated with acetone; Figure 4 It can be seen that the PVP / LLTO-CNW coaxial nanowires after acetone treatment have obvious PVP sheath.

[0115] like Figure 5 As shown, it is a scanning electron microscope image of the PVP / LLTO-NW uniaxial nanowire obtained in step 1) of comparative example 1 of the present invention; Figure 5It can be seen that the average diameter of PVP / LLTO-NW prepared by uniaxial electrospinning technology is small, about 700 nm.

[0116] like Figure 6 As shown, it is a scanning electron microscope image of the LLTO-CNW nanowire framework obtained in step 2) of Example 1 of the present invention; Figure 6 It can be seen that the LLTO-CNW nanowire framework structure obtained after sintering of PVP / LLTO-CNW prepared by coaxial electrospinning technology is dense and uniform, with an average diameter of about 450nm.

[0117] like Figure 7 As shown, it is a scanning electron microscope image of LLTO-NW obtained in step 2) of comparative example 1 of the present invention; Figure 7 It can be seen that the LLTO-NW nanowires obtained after sintering of PVP / LLTO-NW prepared by uniaxial electrospinning technology have a large number of pores and voids outside the frame, and the average diameter is about 250nm.

[0118] like Figure 8 As shown, the LLTO-CNW nanowire framework of Example 1 of the present invention, the LLTO-NW of Comparative Example 1, and the LLTO nanoparticles (Li prepared by a mature sol-gel method according to the molar ratio of Ti(OC4H9)4, LiNO3, and La(NO3)3·6H2O of 1:0.38:0.557) 0.33 La 0.557 XRD spectrum of TiO3 nanoparticles (denoted as LLTO-NP); Figure 8 It can be seen that the (001) / (110) peak intensity ratio of LLTO-CNW is 5.4%, which is much lower than 10.2% of LLTO-NP and 16.2% of LLTO-NW, indicating that the proportion of (001) crystal planes perpendicular to the c-axis in LLTO-CNW is reduced, the number of (110) crystal planes growing along the c-axis direction is increased, and the c-axis with the fastest lithium ion transfer ability is significantly increased.

[0119] like Fig. 9 As shown, it is a scanning electron microscope image of the high-performance oriented crystal nanowire composite solid electrolyte PL / LLTO-CNW obtained in step 4) of Example 1 of the present invention; Fig. 9 It can be seen that the high-performance oriented crystal nanowire composite solid electrolyte PL / LLTO-CNW is uniform and dense, with a thickness of about 50 μm.

[0120] like Fig.10 As shown, the ionic conductivity diagram of the PL / LLTO-CNW electrolyte of Example 1 of the present invention, the PL / LLTO-NW electrolyte of Comparative Example 1, and the PL electrolyte of Comparative Example 2; Fig.10It can be seen that the ionic conductivity of the high-performance oriented crystal nanowire composite solid electrolyte PL / LLTO-CNW reaches 1.29×10 -4 S cm -1 , at 60℃, it reaches 1.32×10 -3 S cm -1 , respectively, PL electrolyte (3.51×10 -6 S cm -1 , 3.31×10 at 60℃ -4 S cm -1 ) by 36 times and 4 times. In contrast, due to the LLTO-NW nanowire Li + The transfer capacity and dissociation degree of lithium salt in the polymer matrix are low, and the ionic conductivity of PL / LLTO-NW electrolyte is only 5.13×10 -5 S cm -1 At 60℃, the ionic conductivity is only 8.79×10 -4 S cm -1 .

[0121] Fig.11 As shown, it is a room temperature cycle performance diagram of an all-solid-state lithium battery assembled with the PL / LLTO-CNW electrolyte of Example 1 of the present invention, the PL / LLTO-NW electrolyte of Comparative Example 1, and the PL electrolyte of Comparative Example 2; Fig.11 It can be seen that the LFP|PL / LLTO-CNW|Li battery assembled by the high-performance oriented crystal nanowire composite solid electrolyte PL / LLTO-CNW can operate stably at 25°C for 300 cycles and still has a capacity of 120.8 mAh g -1 The high discharge capacity and high capacity retention rate of 96.8% for the LFP|PL / LLTO-NW|Li battery (Comparative Example 1) can only maintain 91.6 mAh g after 300 cycles. -1 The discharge capacity of the LFP|PL|Li battery (Comparative Example 2) was only 79.3%.

[0122] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-performance oriented crystal nanowire composite solid electrolyte, characterized in that: The following steps are involved: S1, Preparation of coaxial nanowires with "core-sheath" structure: S1.1, dissolving PVP in DMF to obtain PVP spinning solution; S1.2, dissolving Ti(OC4H9)4, LiNO3, La(NO3)3·6H2O and acetic acid in DMF to obtain LLTO precursor solution; S1.3, using the PVP spinning solution obtained in step S1.1 as the sheath solution, and the LLTO precursor solution obtained in step S1.2 as the core solution, spinning the above solutions on a rotating drum receiver using coaxial electrospinning technology under high voltage electric field conditions at different propulsion speeds; after drying, PVP / LLTO-CNW coaxial nanowires with a "core-sheath" structure are obtained; S2, sintering the PVP / LLTO-CNW coaxial nanowires in an air atmosphere to obtain an LLTO nanowire framework with an oriented crystal structure; S3, preparation of polymer electrolyte solution: dissolving polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide in an acetonitrile solvent under an inert gas atmosphere to obtain a polymer electrolyte solution; S4, repeatedly dropping the polymer electrolyte solution into the LLTO nanowire framework with a directional crystal structure under an inert gas atmosphere and drying until the LLTO nanowire framework is completely embedded in the polymer matrix; finally vacuum drying is performed to obtain a high-performance directional crystal nanowire composite solid electrolyte.

2. The method for preparing a high-performance oriented crystalline nanowire composite solid electrolyte according to claim 1, characterized in that: In the step S1.1, the average molecular weight of PVP is 1.3 million; and in the PVP spinning solution, the mass fraction of PVP is 10-22%.

3. The method for preparing a high-performance oriented crystalline nanowire composite solid electrolyte according to claim 1, characterized in that: In the step S1.2, the molar ratio of Ti(OC4H9)4, LiNO3, and La(NO3)3·6H2O is 1:0.38:0.557; the mass sum ratio of Ti(OC4H9)4, LiNO3, and La(NO3)3·6H2O to DMF is 1.2-2.2:1, and the unit for comparison is g:mL; the volume ratio of DMF to acetic acid is 1:0.05-0.

3.

4. The method for preparing a high-performance oriented crystalline nanowire composite solid electrolyte according to claim 1, characterized in that: In the step S1.3, the sheath solution is advanced at a speed of 0.2 to 0.8 mL / h, and the core solution is advanced at a speed of 0.05 to 0.4 mL / h.

5. The method for preparing a high-performance oriented crystalline nanowire composite solid electrolyte according to claim 1, characterized in that: In the step S1.3, the voltage of the high voltage electric field is 10-20 kV, and the rotation speed of the drum receiver is 100-900 r / min.

6. The method for preparing a high-performance oriented crystalline nanowire composite solid electrolyte according to claim 1, characterized in that: In the step S2, the sintering temperature is 800-1100°C, the sintering and heat preservation is 1-4 hours, and the heating and cooling rate of the sintering process is 1-10°C / min.

7. The method for preparing a high-performance oriented crystalline nanowire composite solid electrolyte according to claim 1, characterized in that: In the step S3, the molecular weight of polyethylene oxide is 300,000 to 2,000,000, and the mass ratio of polyethylene oxide to lithium bis(trifluoromethanesulfonyl)imide is 2 to 5:1; in the polymer electrolyte solution, the concentration of polyethylene oxide is 1 to 6 mg / mL.

8. The method for preparing a high-performance oriented crystalline nanowire composite solid electrolyte according to claim 1, characterized in that: In step S4, the drying temperature of the drying step is 30-55° C., and the drying time for each drying step is 0.5-3 hours; the drying temperature of the vacuum drying process is 50-70° C., and the drying time is 24-72 hours.

9. The method for preparing a high-performance oriented crystalline nanowire composite solid electrolyte according to claim 1, characterized in that: The mass fraction of the LLTO nanowire framework in the high-performance oriented crystalline nanowire composite solid electrolyte obtained in step S4 is 30-75%, and the thickness of the high-performance oriented crystalline nanowire composite solid electrolyte is 20-120 μm.

10. Use of a high-performance oriented crystal nanowire composite solid electrolyte prepared by the preparation method according to any one of claims 1 to 9 in an all-solid-state lithium battery.